2022
DOI: 10.1002/tpg2.20241
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and molecular analysis reveals that two major loci and their interaction confer clubroot resistance in canola introgressed from rutabaga

Abstract: Clubroot disease caused by Plasmodiophora brassicae is one of the serious threats to canola (Brassica napus L. subsp. napus) production. The evolution of new pathotypes rendering available resistances ineffective compel the introgression of new resistance into canola and extend our understanding of the genetic and molecular basis of the resistance. In this paper, we report the genetic and molecular basis of clubroot resistance in canola, introgressed from a rutabaga (B. napus L. subsp. rapifera Metzg. ‘Polycro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Jiang et al studied the CR locus found in resistant "Kc84R" and identified BnERF034 as one of the CR genes on chromosome A03 [115]. Indeed, many CR loci have been reported, including the ones recently identified by Wang et al, for two QTLs on A03 and A08, conferring resistance to pathotypes 3H, 3A, and 3D in turnip [116]. The development of markers and identification of genomic regions responsible for clubroot resistance laid an important foundation for marker-assisted breeding for the generation of resistant cultivars with durable resistance to clubroot disease.…”
Section: Genomic and Molecular Markers Associated With Clubroot Resis...mentioning
confidence: 99%
“…Jiang et al studied the CR locus found in resistant "Kc84R" and identified BnERF034 as one of the CR genes on chromosome A03 [115]. Indeed, many CR loci have been reported, including the ones recently identified by Wang et al, for two QTLs on A03 and A08, conferring resistance to pathotypes 3H, 3A, and 3D in turnip [116]. The development of markers and identification of genomic regions responsible for clubroot resistance laid an important foundation for marker-assisted breeding for the generation of resistant cultivars with durable resistance to clubroot disease.…”
Section: Genomic and Molecular Markers Associated With Clubroot Resis...mentioning
confidence: 99%
“…'Brookfield', which was resistant to all five 'old' pathotypes (2F, 3H, 5I, 6M, and 8N) found in Canada prior to the introduction of clubroot-resistant canola. Wang et al [35] used a rutabaga cv. 'Polycross' as a resistance donor to breed for canola populations resistant to three Canadian pathotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two major ( Rcr11 and Rcr13 ) and one minor QTL ( Rcr_C03-4 ECD10 ) were identified for resistance to 12 pathotypes (3A, 2B, 5C, 3D, 8E, 5G, 3H, 8J, 5L, 3O, 8P, and 5X) of Plasmodiophora brassicae in the B. napus cultivar ECD10 through genotyping-by-sequencing 18 . Identification of major genes conferring resistance to Canadian pathotypes in Brassica species has been also conducted at the University of Manitoba 19 , 20 and the University of Alberta 21 27 . However, these major genes typically provide qualitative resistance, which is considered race-specific and can be rapidly overcome by the pathogen.…”
Section: Introductionmentioning
confidence: 99%